The Effect of Learning Strategy, Achievement Motivation, and Communication Skill toward Learning Outcomes on the Course PMPIPS-SD at PGSD - Herianto, Edy (International Research Journal of Management, IT & Social Sciences, 2017)
The Effect of Instructional Strategies, Achievement Motivation, and Communication Skills toward Learning Outcomes of PGSD on PGSD. The purpose of this research were to compare the effectiveness of the use of instructional strategies, achievement motivation, and communication skills of PGSD students in the PMPIPS-SD subject. A quasi-experimental research with pretest-posttest nonequivalent control group design was carried out to achieve the goals. The data were analyzed by three-way ANOVA with SPSS 16,0 for windows. The research result showed that the learning outcomes students of the PMPIPS-SD subject taught by using PK-IK strategy was better than that using PN-DK strategy, the students who had high achievement motivation better than who had low one, the students who had high communication skills better than who had low one.